Induction of Apoptosis and Cytotoxicity by Raphasatin in Human Breast Adenocarcinoma MCF-7 Cells - Muhammad Din Ibrahim; Saie Brindha Kntayya; Nooraini Mohd Ain; Renato Iori; Costas Ioannides; Ahmad Faizal Abdull Razis (Molecules, 2018)
Glucoraphasatin (GRH), a glucosinolate present abundantly in the plants of the Brassicaceae family, is hydrolyzed by myrosinase to raphasatin, which is considered responsible for its cancer chemopreventive activity; however, the underlying mechanisms of action have not been investigated, particularly in human cell lines. The aims of this study are to determine the cytotoxicity of raphasatin, and to evaluate its potential to cause apoptosis and modulate cell cycle arrest in human breast adenocarcinoma MCF-7 cells. The cytotoxicity was determined following incubation of the cells with glucoraphasatin or raphasatin (0⁻100 µM), for 24, 48, and 72 h. GRH displayed no cytotoxicity as exemplified by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. When myrosinase was added to the incubation system to convert GRH to raphasatin, cytotoxicity was evident. Exposure of the cells to raphasatin stimulated apoptosis, as was exemplified by cell shrinkage, membrane blebbing, chromatin condensation, and nuclear fragmentation. Moreover, using Annexin V-FITC assay, raphasatin induced apoptosis, as witnessed by changes in cellular distribution of cells, at different stages of apoptosis; in addition, raphasatin caused the arrest of the MCF-7 cells at the G2 + M phase. In conclusion, raphasatin demonstrated cancer chemopreventive potential against human breast adenocarcinoma (MCF-7) cells, through induction of apoptosis and cell cycle arrest.